PENYEBAB, DAMPAK, DAN PBEDIKSI DARI FINANCIAL DISTRESS SERTA SOLUSI UNTUK MENGATASI FINANCIAL DISTRESS - Dwijayanti, S. Patricia Febriml (Widya Mandala Surabaya Catholic University, 2010)
Financial distress is a condition thert shows the stages of decline in the company's financial condition that occurred prior to the bankruptcy or liquidation (often called liquidation bankruptcy or closure of companies or company insolvency) or the inability of companies to pay financial obligations that have matured. Conditions of financial distress avoid by the company, because it lead to bankruptcy if the management company can not afford to take appropriate action to resolve existing financial problems. This paper will discuss the causes, impact and how to make the prediction of financial distress, several ways to predict, and the benefits of predicting financial distress as well as solutions for management.